2004
DOI: 10.1080/01431160310001654437
|View full text |Cite
|
Sign up to set email alerts
|

Is the Amik Basin (SE Turkey) a triple-junction area? Analyses of SPOT XS imagery and seismicity

Abstract: In the eastern Mediterranean, plate motions occur between the Arabia/Anatolia, Africa/Arabia and Anatolia/Africa boundaries along the Amanos Fault, the Dead Sea Fault and the Cyprus Arc, and the extension of the latter on land. Detailed enhancement and classification procedures applied to SPOT XS imagery of the Hatay region, and centred on the Quaternary Amik Basin, have revealed a prominent NE-SW-trending tectonic lineament. Recent seismicity suggests that this NE-SW-trending lineament dies out in the Quatern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…Antakya located in the Eurasian, African and Arabian tectonic interaction zone, forming a triple junction area (Over et al 2004b), is the seismically dangerous region. Antakya, the largest city of a former civilization (i.e., Mesopotamian), had been demolished many times by earthquakes in its history (Table 1); the last two (Ergin et al 1967).…”
Section: Seismicity Of the Regionmentioning
confidence: 99%
“…Antakya located in the Eurasian, African and Arabian tectonic interaction zone, forming a triple junction area (Over et al 2004b), is the seismically dangerous region. Antakya, the largest city of a former civilization (i.e., Mesopotamian), had been demolished many times by earthquakes in its history (Table 1); the last two (Ergin et al 1967).…”
Section: Seismicity Of the Regionmentioning
confidence: 99%
“…To better define active fault belts in recent years, in addition to studies in the field, detailed observations of satellite images are made in the computer environment (Adıyaman et al, 2001) and data are assessed together. Though lineation analysis with remote sensing methods is a commonly-used research method in geological research (Süzen and Toprak, 1998;Över et al, 2004), lineations produced by this analysis only represent broken lines (Karaca et al, 2003). Structural lineations formed by linear features like valleys and ridges contain important elements to define nature and topography (O'Leary et al 1976).…”
Section: Determination Of Structural Elements In the Study Area With mentioning
confidence: 99%
“…Saroglu et al (1992) defined a triple junction in the vicinity of Antakya between the EAF and DSF plate boundaries and a small NNW-SSE-trending dextral local segment, named the Reyhanlı Fault, which evidently does not represent any plate, sub-plate or block boundary. Over et al (2004) suggested that major faults, which are proximal to each other in the vicinity of the Amik Basin, form a triple junction (Antakya triple junction) to accommodate deformation between Arabia/Anatolia, Africa/Arabia and Anatolia/Africa.…”
Section: Geology and Tectonic Structure Of The Hatay Regionmentioning
confidence: 99%
“…5b). The Cilicia region has very complex tectonism and lies in an intersection domain among three active belts: the southern end of the left-lateral East Anatolian Fault (EAF), the northern end of the left-lateral Dead Sea Fault (DSF), and the Cyprus Antakya Transform (CAT) (Over et al, 2004). This domain accommodates the relative motions of Arabia/Anatolia, Africa/ Arabia and Anatolia/Africa (Mc Kenzie, 1972;Mc Kenzie, 1976;Le Pichon and Angelier, 1979;Şengör, 1979;Jackson and McKenzie, 1984;Dewey et al, 1986;Westaway, 1994).…”
Section: Geology and Tectonic Structure Of The Hatay Regionmentioning
confidence: 99%